Strategi Pembelajaran Kooperatif Pada Mata Kuliah Penataan Rambut - Aniesa Puspa Arum (JTP - Jurnal Teknologi Pendidikan, 2020)
This study aims to design and develop cooperative learning strategies in hairstyling subjects in order to increase motivation and learning involvement of students through the implementation of cooperative learning strategies. This type of research is research and development (R&D) using the 4D development model that aims to find, design, develop and disseminate the products produced so that they can be used in the learning process to improve student learning outcomes. The result of this research is design cooperative learning strategy in hairstyling subject, based on the characteristics and components of structured learning strategy.